Rubicon prevents autophagic degradation of GATA4 to promote Sertoli cell function - Tadashi Yamamuro; Shuhei Nakamura; Yu Yamano; Tsutomu Endo; Kyosuke Yanagawa; Ayaka Tokumura; Takafumi Matsumura; Kiyonori Kobayashi; Hideto Mori; Yusuke Enokidani; Gota Yoshida; Hitomi Imoto; et al. (PLoS Genetics, 2021)
Autophagy degrades unnecessary proteins or damaged organelles to maintain cellular function. Therefore, autophagy has a preventive role against various diseases including hepatic disorders, neurodegenerative diseases, and cancer. Although autophagy in germ cells or Sertoli cells is known to be required for spermatogenesis and male fertility, it remains poorly understood how autophagy participates in spermatogenesis. We found that systemic knockout mice of Rubicon, a negative regulator of autophagy, exhibited a substantial reduction in testicular weight, spermatogenesis, and male fertility, associated with upregulation of autophagy. Rubicon-null mice also had lower levels of mRNAs of Sertoli cell–related genes in testis. Importantly, Rubicon knockout in Sertoli cells, but not in germ cells, caused a defect in spermatogenesis and germline stem cell maintenance in mice, indicating a critical role of Rubicon in Sertoli cells. In mechanistic terms, genetic loss of Rubicon promoted autophagic degradation of GATA4, a transcription factor that is essential for Sertoli cell function. Furthermore, androgen antagonists caused a significant decrease in the levels of Rubicon and GATA4 in testis, accompanied by elevated autophagy. Collectively, we propose that Rubicon promotes Sertoli cell function by preventing autophagic degradation of GATA4, and that this mechanism could be regulated by androgens. Author summary Androgens, known as “male” hormones, stimulate and activate their receptors in various tissues, including testicular cells and skeletal muscle cells, thereby maintaining spermatogenesis and muscle mass. Notably, androgens-dependent maintenance of male reproduction is of particular interest because the incidence of male infertility has increased in recent decades. Previous studies revealed that Androgen receptor knockout in Sertoli cells causes defective spermatogenesis, indicating a crucial role of androgens in Sertoli cells. Another study suggested that fatherhood-dependent downregulation of androgens could decrease male fertility, leading the male to concentrate on parenting existing offspring. However, it remains largely unknown how androgen regulates Sertoli cell function for male reproduction. In the present study, our results suggest that androgens regulate testicular levels of Rubicon, a negative regulator of autophagy, to control autophagic degradation of GATA4 that is required for Sertoli cell function. Because autophagy and androgens participate in various cellular processes, we anticipate that this study will provide a solid evidence for understanding such processes.